Sistem Informasi Akuntansi Pencatatan Kas Kecil Menggunakan Metode Extreme Programming - Adi Supriyatna; Irmawati Carolina; Wina Widiati (LPPM Universitas Bina Sarana Informatika, 2021)
Petty cash is a fund set by the company to finance the company's regular operations whose total expenditure is relatively smaller and paid in cash without the use of bank transfers or checks. In a Petty cash recording company both cash in and out is the responsibility of the accounting part, in its management still using conventional systems such as using ledgers, microsoft excel and so on. This, of course, can lead to errors and take a long time. The goal of the study was to design an effective and efficient web-based petty cash recording accounting information system. The methods used in this study are data collection which includes observation and study of literature and system development methods using Extreme Programming consisting of planning, designing, coding and testing stages. The results of this study show that the use of petty cash recording information systems can provide convenience to users as well as effective and efficient time in the process of recording petty cash, in addition to minimizing data misuse